2019
DOI: 10.1108/lhs-02-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the state of lean and six sigma practices in healthcare in Mexico

Abstract: Purpose The purpose of this study is to assess the state at which lean and six sigma (LSS) are used as a management system to improve the national health system national health system of Mexico. Design/methodology/approach Cross-sectional survey-research. The survey was administered at 30 different hospitals across six states in Mexico. These were selected using convenience sampling and participants (N = 258) were selected through random/snowball sampling procedures, including from top managers down to front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…We found 25 out of 39 studies combining lean with tools and principles of the six sigma methodology, suggesting that such integration offers a more robust approach to improving speed, quality and costs, increasing customer satisfaction, and maximizing shareholder value [ 153 , 154 ]. While lean focuses on reducing waste and NVA activities, six sigma focuses on reducing process variation by following the DMAIC approach (Define, Measure, Analyze, Improve and Control) and by using statistical tools.…”
Section: Discussionmentioning
confidence: 99%
“…We found 25 out of 39 studies combining lean with tools and principles of the six sigma methodology, suggesting that such integration offers a more robust approach to improving speed, quality and costs, increasing customer satisfaction, and maximizing shareholder value [ 153 , 154 ]. While lean focuses on reducing waste and NVA activities, six sigma focuses on reducing process variation by following the DMAIC approach (Define, Measure, Analyze, Improve and Control) and by using statistical tools.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the production of articles on health service topics, we have considered the following literature reviews, conducted for Mexico by Peimbert-García et al (Peimbert-García et al, 2019) and a more general by Vaishnavi, V., & Suresh, M. (Vaishnavi & Suresh, 2020), in which a panorama is presented for the application of Lean Six Sigma (LSS) in health care organizations. Peimbert-García, et al (Peimbert-García et al, 2019) presents an article that provides an overview of the penetration of LSS management practices in the Mexican health care system, through a survey of 30 hospitals in six states of the Republic, to which N = 258 responded, including senior management and frontline staff. It was found that the penetration of LSS initiatives in Mexico's health care system is still in its infancy since only 16% of those surveyed had participated in an LSS initiative, and these were used equally in public and private hospitals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that there were significant differences between the staff of the public hospitals and private hospitals on Lean and Six Sigma initiatives. Peimbert-Garcia et al [ 6 ] assessed the status of Lean & Six Sigma practices in healthcare in Mexico. They observed that only 16% of the respondents had implemented the Lean & Six Sigma projects.…”
Section: Introductionmentioning
confidence: 99%